Targeting lipid metabolism to overcome EMT-associated drug resistance via integrin β3/FAK pathway and tumor-associated macrophage repolarization using legumain-activatable delivery - Hongyue Jin; Yang He; Pengfei Zhao; Ying Hu; Jin Tao; Jiang Chen; Yongzhuo Huang (2018)
Epithelial-mesenchymal transition (EMT) is closely associated with the development of drug resistance.Lipid metabolism plays an important role in EMT.This work was to study the cholesterol-lowering drug simvastatin for reversing EMT-associated resistance to chemotherapy via lipid metabolism.Methods: The combination of simvastatin and paclitaxel was used to overcome the EMT-associated drug resistance.For dual-action on both cancer cells and tumor-associated macrophages (TAM), the tumor microenvironment-activatable multifunctional liposomes were developed for drug codelivery.The liposomes were modified with a hairpin-structured, activatable cell-penetrating peptide that is specifically responsive to the tumor-associated protease legumain.Results: It was revealed simvastatin can disrupt lipid rafts (cholesterol-rich domains) and suppress integrin-β3 and focal adhesion formation, thus inhibiting FAK signaling pathway and re-sensitizing the drug-resistant cancer cells to paclitaxel.Furthermore, simvastatin was able to re-polarize tumor-associated macrophages (TAM), promoting M2-to-M1 phenotype switch via cholesterol-associated LXR/ABCA1 regulation.The repolarization increased TNF-α, but attenuated TGF-β, which, in turn, remodeled the tumor microenvironment and suppressed EMT.The liposomal formulation achieved enhanced treatment efficacy.Conclusion: This study provides a promising simvastatin-based nanomedicine strategy targeting cholesterol metabolism to reverse EMT and repolarize TAM to treat drug-resistant cancer.The elucidation of the molecular pathways (cholesterol/lipid raft/integrin β3/FAK and cholesterol-associated LXR/ABCA1 regulation) for anti-EMT and the new application of simvastatin should be of clinical significance.